Produção de biossurfactantes por Bacillus amyloliquefaciens IT45 - Lima, Frederico Alves (2017)
Biosurfactants are molecules of microbial origin that have superficial action. Among the most effective are the lipopeptide biosurfactants produced by Bacillus, especially surfactin. These biological products have a number of advantages that potentiate their applications, such as: stability to extreme conditions (pH, temperature), diversity of chemical structures, excellent surface and ecological properties, antibiotic action against pathogenic microorganisms, etc. In this context, the productions of total biosurfactants and Surfactin by Bacillus amyloliquefaciens IT45 were evaluated when the reagents concentration present in the culture medium varied. The submerged fermentations were carried out in an industrial shaker and in a pilot bioreactor of 40 liters capacity. In order to improve the reactants concentration, a Central Composite Design was developed to evaluate the influence of three variables (glucose syrup – Glucodry, yeast extract and calcium chloride) on superficial tension, total biosurfactant production and residual sugar. After statistical analyzes, when the variables were in the concentrations (g.L-1) of 20 for Glucodry, 15 for yeast extract and 4 for calcium chloride, the superficial tension (mN/m) reduces values above 50 to about 30, the residual sugar was minimal, around 31% and the total biosurfactant production was maximum, around 5.5 gL-1, after a period of 48 hours. The characterization of the biosurfactant identified Surfactin presence that was quantified in the retention time of 13.5 minutes. In order to know the real production of Surfactin and cellular biomass growth, fermentations were made in a 40 liter pilot bioreactor and the results were quite favorable. The most important culture medium suggested by the Central Composite Design, where glucose syrup, yeast extract and calcium chloride were in the concentrations (g.L-1) of 20, 15 and 4, respectively. For this fermentation, the cellular growth was 6.0 x 109 CFU.mL-1, Surfactin production was 0.63 g.L-1 and residual sugar was 28%. The results demonstrate that Bacillus amyloliquefaciens IT45 has potential to produce biosurfactants and does not require high concentrations of carbon and nitrogen sources for its development.